The Effectiveness of Influencers in Recapturing Former Customers for Big Brands - Nurhikmah, Shara (Celebes Scholar pg, 2023)
This has a look at targets to quantitatively analyze the suitability of the influencers in the restoration of the previous purchasers for the massive manufacturers. In extending the effect of influencer attributes which involve engagement stage, credibility and authenticity and types of content material, promotional, academic and experiential on recapture achievement, the examine identify factors that influence customers’ go back behavior. It has been found out that measures of engagement level and authenticity are the two best predictors of recapture effectiveness of the overall engagement and promotional content is found most useful for quick outcomes. The look at also points to the large impact that logo type has on recapture effects; influencer profiles should therefore mirror logo values. These outcomes offer practical recommendation for manufacturers keen on to appropriate the influencer advertising and marketing approaches that they used and how to hyperlink transient and extent content material approaches to boost the shoppers’ participation and loyalty.